Mineralisation and bioavailability of phosphorus from poultry manure and sewage sludge-based phospho-composts for maize production - Chauke, Rhandu (University of Limpopo (Turfloop Campus), 2014)
Phospho-composts of different mix ratios (5:5, 7:3, 8:2 and 9:1) were produced through thermophilic co-composting of poultry manure (PM) and sewage sludge (SS) with ground phosphate rock (GPR). Composted PM and SS without GPR addition were included as control. Cured phospho-composts were chemically characterised and used for both laboratory incubation and greenhouse studies, respectively for phosphorus (P) mineralisation and bioavailability, over a period of 42 days. Results revealed that Bray-P1 concentration measured in compost amended soils at 14, 21 and 42 DAI differed significantly (P<0.05) and ranged between 5.47 and 11.14 mg kg-1 and between 5.28 and 11.78 mg kg-1 in poultry manure and sewage sludge-based phospho-composts, respectively. The maximum amount of cumulative P mineralised of 16.06 and 9.98 mg kg -1, respectively in PM and SS-based phospho-composts were obtained from the 8:2 mix ratio. The content of the acid detergent fibre of the different phospho-composts showed positive and significant correlation with cellulose, lignin and total organic carbon (TOC). Similarly, cellulose as well as C:P ratio showed significant correlation with both lignin and TOC. The polynomial relationship between cumulative P mineralised and the various GRP and manure mix ratios revealed significant and positive R2- values of 0.731 and 0.613 for PM and SS-based phospho-composts, respectively. The maximum amount of maize tissue P uptake of 0.12 and 0.11 mg pot-1 in PM and SS-based phospho-compost respectively were also obtained from the 8:2 mix ratio while the least amount of 0.04 mg P pot-1 was obtained from GPR and unamended pots. Maize tissue P uptake following the phospho-compost application was significantly affected by the differences in soil type. Tissue P uptake was 0.06 and 0.11 mg P/pot, respectively in low potential and high potential soils with a significantly higher value. The use of the different phospho-composts showed great potential for amelioration of P-deficiency problems in crops while thermophilic cocomposting improved the solubility and bioavailability of P from non-reactive GPR. Keywords: Ground phosphate rock; poultry manure; sewage sludge; phosphocomposts; phosphorus mineralisation; soil fertility management.
Thesis (MSc. Agriculture (Soil Science)) -- University of Limpopo, 2014
Keywords: Phosphorus composts; Poultry manure; Phosphorus -- Bioavailability; Phosphorus in agriculture; Poultry -- Manure; Sewage sludge as fertilizer